PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP FINANCIAL DISTRESS DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI - Regita Wanda Puspita; Poppy Dian Indira Kusuma (LPPM PoliteknikPratamaKendal- Universitas Sains Dan Teknologi Komputer, 2025)
This research investigates the influence of governance structures specifically board composition, audit committee presence, and the ratio of independent commissioners on the likelihood of financial distress within Indonesia's agribusiness sector, incorporating profitability as a moderating factor. The central concern of this study is the persistent threat of financial instability that may culminate in bankruptcy, thus underlining the necessity for robust organizational oversight. A quantitative method was applied, utilizing secondary data sourced from financial reports of agribusiness firms listed on the Indonesia Stock Exchange (IDX) during the 2020–2022 period. Analytical techniques employed include multiple linear regression and moderated regression analysis (MRA) to evaluate the interaction between profitability and governance elements. The findings reveal that both board size and audit committee activity exhibit a significant inverse relationship with financial distress, whereas independent commissioner representation lacks statistical impact. Moreover, profitability enhances the mitigating role of governance mechanisms against financial vulnerability. These insights affirm the relevance of strengthening internal governance and financial health as preventive measures against financial crises in the agribusiness industry